Healthcare utilization for somatic conditions among Swedish patients in opioid substitution treatment, with and without on-site primary healthcare - Teodor Vikbladh; Katja Troberg; Anders Håkansson; Disa Dahlman (BMC, 2022)
Abstract Background Opioid substitution treatment (OST) populations are aging and have increased mortality and somatic morbidity compared to general populations internationally. While OST patients have poor self-rated physical health and unmet healthcare needs, documented healthcare utilization has been sparsely investigated. The aim of this study was to assess registered healthcare utilization for somatic conditions in a sample of Swedish OST patients, and compare healthcare utilization among OST patients with and without use of on-site primary healthcare (PHC). Methods Patients in OST in Malmö, Sweden, were recruited for a survey study conducted in 2017-2018. Survey data were compared with comprehensive patient records from specialized and primary care during one year prior to study inclusion (total n = 190). All patient records were examined for healthcare utilization, source of healthcare (PHC, emergency care and secondary care), and documented diagnoses and symptoms. Factors associated with healthcare utilization were analyzed by using logistic regression analysis. Patients with and without on-site PHC were compared by using descriptive statistics and Chi-2 test. Results A total of 88% of the sample had been in direct or indirect contact with somatic healthcare during one year (PHC 66%; emergency care 28%; secondary care 67%). The most prevalent somatic diagnoses were infectious diseases (39%) and symptom diagnoses (37%). Respiratory, dermatological and musculoskeletal diagnoses, and trauma/intoxication were documented in 21-26% of the sample, respectively. PHC utilization was associated with older age and being born in Sweden. Among patients with on-site PHC (n = 25), the number utilizing secondary care was 84%, and certain diagnostic codes were more frequent in this group. Conclusion OST patients are seemingly underserved as regards their physical health. Since increased OST access decreases opioid overdose fatalities, the life expectancy among OST patients is likely to increase and thereby also increases the risk of age-related conditions. Thus, easily accessible physical healthcare is of great importance in this group. On-site PHC might be a way to establish healthcare contact with OST patients, especially for non-acute conditions, although further research is needed.